The Deceased Transplant Recipients: A Forgotten Source of Organ Donors - Dai D. Nghiem (Uro, 2023)
Background: Organ transplantation is the most successful therapy for end-stage organ disease since it increases the quality of life and life expectancy. For these reasons, over 107,000 patients were on the waitlist in the United States for a transplant in 2022. Unfortunately, only 42,887 transplants were performed, and annually, over 7000 patients on the kidney list die or are too sick to transplant. To solve this severe organ shortage, the use of the deceased transplant recipients with functioning organs, whether transplanted or native, is explored as a new source of organ donors. Methods: To assess the feasibility of this option, first, we will review the rate of kidney transplant recipients dying with functioning grafts (DWGF), their re-use, the organ allocation system, the technical aspects of the organ procurement, and the transplantation of the DWGF kidneys. Then, we will consider the larger group of all deceased transplant recipients as potential donors for all functioning, native, or transplanted organs. Conclusions: (1). All functioning kidney transplants explanted from the deceased transplant recipients have excellent long-term function after re-transplantation. (2). The other functioning organs constitute a large unrecognized pool of transplantable organs. (3). The intensivists and the transplant community should be educated about these new options to improve the organ shortage.